Internationalization and financial federalism: The United States and Germany at the crossroads? - Richard Deeg; Susanne Lütz (Max-Planck-Institut für Gesellschaftsforschung, 1998)
In this paper we examine some effects of economic internationalization on state structures, especially in regard to the distribution of power and authority within federalist systems. Using an institutional rational choice model, we analyze changes in financial regulation and market structures in Germany and the United States. Our focus is on the financial realm because of its high degree of internationalization and because in both countries financial markets and regulation have historically exhibited federalist traits. Our findings indicate that internationalization has led to significant convergence in financial market structures and regulation across the two countries and that in each case this convergence has been accompanied by centralization of financial regulatory authority. While both the German type of cooperative federalism and the American model of competitive federalism proved to be vulnerable to the growing international pressures, the two countries took different paths of change that reflect differences in domestic institutions. Thus we conclude that convergence is, and will likely remain, of a limited nature. – – Dieser Beitrag untersucht die Effekte ökonomischer Internationalisierung auf Staatsstrukturen und auf die Machtverteilung zwischen verschiedenen Ebenen föderaler Systeme. Mit Hilfe einer Rational-choice-Perspektive des institutionellen Handelns werden Veränderungen in Struktur und Regulierung nationaler Finanzmärkte am Beispiel Deutschlands und den Vereinigten Staaten behandelt. In beiden Ländern unterliegt der Finanzsektor erheblichem Internationalisierungsdruck und ist gleichzeitig durch eine ausgeprägt föderale Struktur gekennzeichnet. Unsere Ergebnisse verweisen auf beträchtliche Konvergenz von Marktstrukturen und Regulierungsmodi in beiden Ländern, welche mit der Zentralisierung von Regulierungskompetenzen auf der Bundesebene verbunden ist. Sowohl der deutsche kooperative Föderalismus als auch das amerikanische Modell des Wettbewerbsföderalismus erweisen sich also als anfällig gegenüber wachsendem Internationalisierungsdruck, dennoch schlagen beide Länder unterschiedliche Reformpfade ein, welche Ausdruck des jeweiligen nationalen Institutionengefüges sind. Die Dynamik von Konvergenzprozessen wird (wohl auch zukünftig) institutionell eingedämmt.
Keywords: 300